An 83-GHz High-Gain SiGe BiCMOS Power Amplifier Using Transmission-Line Current-Combining Technique - Chen, Austin Ying-Kuang; Baeyens, Y.; Young-Kai Chen; Jenshan Lin (IEEE transactions on microwave theory and techniques, 2013)
An 83-GHz two-stage cascode power amplifier (PA) implemented in a low-cost 200/180-GHz fT / f max 0.18-μm SiGe BiCMOS technology is presented. The power-combining technique based upon a low-loss two-way transmission-line current combiner has been employed that simultaneously addresses the gain requirement at millimeter wave while delivering a high linear output power, making it a potential contender for multigigabit/second point-to-point data links. The combiner efficiency and large-signal power bandwidth (BW) are improved by the compact output matching network synthesized and excellent amplitude/phase balance of the proposed current combiner, which also considers the reliability issues such as electromigration and built-in redundancy during power device failure. At 83 GHz, the PA achieves a measured saturated power (P sat ) of 14.7 dBm, output-referred 1-dB compression point (OP 1dB ) of 12.5 dBm, peak power-added efficiency of 8.1%, and 1-dB large-signal power BW from 75 to 88 GHz. The measured peak power gain (S 21 ) is 25 dB with a 3-dB small-signal BW from 76.8 to 86.4 GHz while consuming a total dc power of 348 mW from a 4-V supply. The overall chip area is 610 μm × 560 μm (0.34 mm 2 ).